A double-blind, randomized study comparing postoperative pain management using epidural ropivacaine with intravenous ketorolac or intravenous ketorolac alone following transabdominal hysterectomy - Chinachoti T. (2014)
Objective: The aim of this study is to compare the effect on postoperative pain of epidural ropivacaine in combination with intravenous ketorolac with intravenous ketorolac alone following transabdominal hysterectomy. Design: A multi-center, randomized, double-blind study was conducted in Thailand and the Philippines to assess postoperative pain management in 107 patients given ketorolac alone or in combination with epidural ropivacaine following transabdominal hysterectomy. Pain score was assessed using a 100-mm visual analogue pain scale (VAS). Results: The VAS scores for pain on coughing and at rest were significantly better in the ropivacaine group. The number of patients who asked for morphine in addition was higher in the ketorolac group compared to the ropivacaine + ketorolac group. The time taken to carry out the first three ambulatory steps was similar for both the two treatment groups. A higher degree of motor block was observed in the ropivacaine group over time. The adverse events observed were similar in both groups. Conclusion: We demonstrated that epidural infusion of ropivacaine in addition with intravenous ketorolac gave superior pain relief at rest and on coughing in patients undergoing transabdominal hysterectomy when compared to the group receiving intravenous ketorolac alone.